Case Report: Hemangioblastoma- Like Clear Cell Stromal Tumor of the Left Lower Lung - Zhang, Xiaowei; Huang, Bifei; Jiang, Hongquan; Wei, Hangping (Frontiers in Medicine, 2022)
Abstract Background: Haemangioblastoma-like clear cell stromal tumour (HLCCST) is a recent reports neoplasm of the lung. Only 13 cases have been reported in four recent studies. Because HLCCST is very rare，it has not been included in the 2021 WHO classification of lung tumours. Case presentation: We report a case of HLCCST of the left lower lung in a 40-year-old female who was admitted to our hospital after pulmonary nodules were discovered. Plain chest computed tomography scan showed a nodular high-density shadow measuring approximately 8 mm in diameter in the left lower lobe. The lesion had clear borders, uneven internal density, and a low-density central vacuolar area. Partial resection of the left lower lobe by video-assisted thoracoscopic surgery. Post-operative histopathologic diagnosis read “haemangioblastoma-like clear cell stromal tumour” of the left lower lung. Conclusion: HLCCST is an extremely rare tumour and needs long term follow-up after operation. Clinically, it may be easily confused with other benign and malignant tumours of the lung, and diagnosis is solely determined by histopathologic examination。This case prompt that immunohistochemical CD34 can be strong positive.